Quo Vadis Pengembalian Benda Sitaan Berupa Harta Bukan Hasil Tindak Pidana Pencucian Uang Kepada Korban - Lisanawati, Go; Amelinda Charlotte, Florence (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2024)
Law Number 8 of 2010 does not explicitly regulate the assets of the proceeds of money laundering. The purpose of this paper is to analyze the return of confiscated objects in money laundering cases as one of the things that must be done in criminal procedure law. In essence, the return of confiscated objects must first fulfil the elements of objects that can be confiscated according to the Criminal Procedure Code and Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes. This research uses normative juridical legal research methods with statutory and conceptual approaches. The legal materials used in this writing are primary legal materials in the form of laws and regulations and secondary legal materials in the form of related books and journals. The problem that arises in this research is the return of confiscated objects to victims who are not entitled to property that was not obtained from the proceeds of a criminal offence. The results showed that there were problems in returning confiscated objects to victims carried out by law enforcement officials, and this violated the laws and regulations, so the defendant's right to his property was deprived. Therefore, there is a need for evaluation and an in-depth understanding of law enforcement officials' implementation of criminal procedure law in Indonesia. Keywords: Evidence; Property Not Proceeds of Crime; Money Laundering; Return of Confiscated Property; Quo Vadis